2018
DOI: 10.1111/age.12674
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HOXC8 in crested Swiss chicken

Abstract: The crest in chicken consists of elongated and upraised feathers, as seen in various breeds such as the Silkie chicken. Recently, the still unknown causative mutation for the crest phenotype was assigned to chromosome 33 and an ectopic expression of HOXC8 was shown. The aim this study was to evaluate whether the crest phenotype in a local Swiss chicken breed, the Appenzeller Spitzhaubenhuhn, is associated with HOXC8. Three previously reported crest-associated flanking markers at the HOXC8 locus were genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Slight differences appeared in ways of expressing the Crest phenotype (Bartels, 2003). For example, unlike a full crest that grows all over the head as seen in the Silkie chicken and Polish chicken, the Appenzeller Spitzhaubenhuhn chicken expresses a helmet‐like crest, with the feathers pointing up straight from the head (Joller et al, 2018). As mentioned above, the feather crest was reported to be closely related to skull protuberance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slight differences appeared in ways of expressing the Crest phenotype (Bartels, 2003). For example, unlike a full crest that grows all over the head as seen in the Silkie chicken and Polish chicken, the Appenzeller Spitzhaubenhuhn chicken expresses a helmet‐like crest, with the feathers pointing up straight from the head (Joller et al, 2018). As mentioned above, the feather crest was reported to be closely related to skull protuberance.…”
Section: Discussionmentioning
confidence: 99%
“…However, Yoshimura et al (2012) proposed a different hypothesis that two different genetic factors separately caused feather crest and cerebral hernia. Moreover, no clear association of three reported Crest markers, HOXC8‐SSR , HOXC8‐3end , and HOXC8‐INTR , was found in Swiss crested chickens, and no polymorphisms were found in exons of HOXC8 (Joller et al, 2018). In addition, Tao et al (2020) suggested that a series of differentially expressed genes (DEGs) existed between crested and noncrested chicken brain regions and eventually identified 547 DEGs, including HOXC10 (Tao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The crest trait is a specific and widely distributed phenotype in birds, but the shape and physiological characteristics of this trait vary among different species of birds. The crest in chickens consists of feathers on the head that are elongated and upraised and differ between breeds in density, size, and shape [7]. The cerebral hemispheres of partially crested chickens are extruded into the spherical region of the skull, and the anterodorsally part of the skull is expanded into a large spherical protuberance, referred to as a "cerebral hernia" [8], but this is not present in all chickens [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the HOXC8 gene was genotyped with the flanking markers HOXC8 -SSR, HOXC8 -3end, and HOXC11 related to coronal protrusions, and no correlation of the reported markers was found in Swiss crested chicken. The two exons of the HOXC8 gene of crested chicken were sequenced, and no polymorphic sites were found in the coding region ( Joller et al., 2018 ). In summary, the molecular genetic mechanism of the chicken crested trait is still unclear, and further research is urgently needed.…”
Section: Introductionmentioning
confidence: 99%